Biochemical responses and proline metabolism in Amaranthus tricolor L. and Phaseolus vulgaris L. under in vitro NaCl Stress - Murugan K; SS, Sunukumar; SR, Harish; GS, Manoj; Krishnan, Remya (Journal of Research in Biology, 2011)
Salinity is currently the major factor which reduces crop yields. One of the biological approaches is to use salt tolerant plants. Amaranthus tricolor L. has been used as a promising plant to ameliorate the salt affected area. The objective of the study is to evaluate the effect of NaCl stress on synthesis and catabolism of proline, soluble proteins, carbohydrates and Na+/K+ ratio in A. tricolor and to compare with the salt-sensitive species, Phaseolus vulgaris L. The experiments were designed with six replications. Seedlings of both species were grown hydroponically with 0, 50, 100, 150, 200, 250 and 300 mM NaCl. The in vitro activity of the enzyme pyrroline 5-carboxylate synthetase under NaCl stress was higher, while, the activity of proline degrading enzyme - proline oxidase showed a reverse trend i.e., low activity in high NaCl concentrations. Soluble protein content was increased in the shoot of A.tricolor but decreased in P.vulgaris. Roots of both the species showed variation in the protein content. Proline content of shoot and roots increased significantly in all the treatments in the plants. However, A.tricolor showed a higher level. The total carbohydrate also showed a similar trend. High level of NaCl decreased the reduced sugar in shoots and roots of the species. Salt stress increased Na+ significantly and decreased the K+ content in both species. The biochemical variation may be interpreted as differential response of the plants to NaCl stress